ANALISIS DAMPAK MONETER, KESIAPAN TEKNOLOGI, DAN ANCAMAN KEAMANAN MATA UANG DIGITAL BANK SENTRAL (CBDC) - Arifah, Ika Diyah Candra; Prasanna, Futari Maysya; Aziz, Muhammad Abdul; Erta, Erta (Universitas Negeri Surabaya, 2022)
Most central banks are exploring central bank digital currencies (CBDCs), and their work continues apace amid the Covid-19 pandemic. Central banks are moving into more advanced stages of CBDC engagement, progressing from conceptual research to practical experimentation. The CBDC (Central Bank Digital Currency) has certain benefits: it is account-based, interest-bearing and universally acceptable. CBDC is a monetary value stored electronically that represents the central bank's obligations and can be used by its users to make payments. This study aims to analyse Garuda's monetary impact, technology readiness and security threats (Indonesian CBDC) based on a systematic literature review conducted from 2020-2022. Publish and Perish are used for collecting articles data, and VosViewer is used for analyzing data that is further to be discussed. This research is expected to contribute knowledge about the state readiness of the CBDC implementation plan based on monetary, technological readiness and banking security perspectives.